Instruments for maintaining the financial stability of territorial self-government entities - Owsiak, Katarzyna (Narzędzia kształtowania stabilności finansowej jednostek samorządu terytorialnego, 2019)
Considerations related to the stability of a financial system include the issue of public finance stability. However, such considerations are often characterised by the inconsistency of terminology, which results from the fact that the concept of public finance stability is used as a synonym of fiscal stability, and, in addition to that, the term is not defined. Undoubtedly, fiscal stability is assessed in the context of the debt limits and deficit levels of the public finance sector. A rapid increase in the indebtedness of territorial self-government entities (part of the total public debt) resulted, among others, from economic slowdown, which indicated that more attention should be given to the financial stability of local government entities. The paper is an attempt to discuss the concept of the financial stability of territorial self-government entities; it proposes a broader approach to the financial stability of territorial self-government entities, and it presents the effectiveness of selected instruments which affect financial stability in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 100-112